PENGARUH DESENTRALISASI FISKAL TERHADAP PERTUMBUHAN EKONOMI : STUDI EMPIRIS DAERAH PANTURA JAWA - , Selli Nelonda, Dr. Akhmad Makhfatih, M.A ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Abstract. The positive contribution of fiscal decentralization to economic growth has been discussed extensively in the last decade. Although the impact of the fiscal responsibility shifting to the lower governments on economic stimulation is favorable from the theoretical perspective, the empirical evidence has always not been successful in substantiating this prediction. This study is aims to see the influence of fiscal decentralization on economic growth in the regional Pantura from 2000 - 2010. The analysis focused on the ratio of own regional revenue to total central government expenditure. This is very critical since the regional autonomy has obliged each region to finance their expenditures. By using data panel estimation from 23 local governments, the fixed effect model, confirms that fiscal decentralization has a positive effect on Java Panturaâs economic growth.